1990
DOI: 10.1164/ajrccm/141.4_pt_1.846
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Synthesis during Lung Development and during Hyaline Membrane Disease in the Nonhuman Primate

Abstract: To assess maturational changes in collagen synthesis, lung tissue was obtained from healthy Macaca nemestrina monkeys at different ages, ranging from 68% of term gestation to adulthood. We hypothesized that infants delivered prematurely have a greater rate of collagen synthesis than do older animals because of their greater rate of lung growth during gestation. Secondly, we hypothesized that lung repair in infants with hyaline membrane disease (HMD) is associated with an additional increase in lung collagen sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Suppression of collagen and other extracellular matrix genes represent a large proportion of suppressed signature genes for matrix fibroblasts after LPS exposure. While the total lung collagen content increases with lung growth and maturation, the synthesis rate of collagen decreases from 80% gestation to full term (35,42). Collagen is responsible for the lung structure, but it does not contribute to the lung compliance and elasticity, which is provided by the elastic fibers -mainly elastin and microfibrils (43).…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of collagen and other extracellular matrix genes represent a large proportion of suppressed signature genes for matrix fibroblasts after LPS exposure. While the total lung collagen content increases with lung growth and maturation, the synthesis rate of collagen decreases from 80% gestation to full term (35,42). Collagen is responsible for the lung structure, but it does not contribute to the lung compliance and elasticity, which is provided by the elastic fibers -mainly elastin and microfibrils (43).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in liquid ventilation have required high proximal airway pressures; experiments in newborn lambs demonstrated that in one protocol the use of peak airwav pressure equal to 31.5 torr was associated with peak alveolar pressure of only 18.6 torr due to a large flow resistive pressure drop of 13 torr along the bronchial tree[12]. Previously in our laboratories, we have studied the impact of conventional and high frequency ventilation on the development of lung injury in prematurelydelivered monkeys[3,32]. Previously in our laboratories, we have studied the impact of conventional and high frequency ventilation on the development of lung injury in prematurelydelivered monkeys[3,32].…”
mentioning
confidence: 99%
“…The composition of pulmonary surfactant and how it changes with fetal maturity and postnatally with HMD was studied [Jackson et al, 1986, 1988]. The pulmonary inflammatory response to preterm delivery and mechanical ventilation was studied [Jackson et al, 1988, 1987] along with lung repair mechanisms [Jackson et al, 1990a,b]. Prenatal steroids were found to accelerate pulmonary development and surfactant production with an increase in lung compliance [Kessler et al, 1982, Truog et al, 1983].…”
Section: Research In Reproductive and Developmental Sciences At The Iprlmentioning
confidence: 99%